The Impact of the Ghana School Feeding Programme on Enrollment, Attendance and Retention in Ga South Municipal Schools - Kamaludeen, H. (University of Ghana, 2014)
The purpose of the study was to examine how the Ghana School Feeding Programme (GSFP) has impacted on enrolment, attendance and retention of children in some beneficiary Basic Schools in Ga South Municipality.The target population for the study was sixty-eight (68) participating schools in the Ga South Municipality of the Greater Accra Region and other stakeholders of the programme. The Public Relation Officer of GSFP, District Desk Officer, School Implementation Committee member, Circuit Supervisor and School Health Programme Officer of GES, School Implementation Committee member, Head Teacher, Class Teacher, Students, Parents and Caterers were the units of analysis. Random and non-random sampling methods were used to select ten schools and a sample size of 105. Questionnaires, semi-structured interview guides, and observation were used to solicit information from the respondents. The research has revealed some successes and failures of the GSFP. Prominent among the successes are; moderate increase in enrolment, attendance and retention; an increase in involvement in learning and cognitive ability of students and employment creation. Areas that need more attention are; Quality and Quantity of Meals; Recruitment of Caterers and Training, Procurement and Value chain, De-worming of beneficiary Students, non-availability of School Kitchen and Canteens and Monitoring and Evaluation. The recommendation of the study shall provide policy makers relevant information that will feed into other educational policy framework(s) that seek to achieve universal basic education in a long run.
Thesis ( Mphil) - University of Ghana, 2014